2021
DOI: 10.1021/acsanm.1c02862
|View full text |Cite
|
Sign up to set email alerts
|

Room-Temperature Hydrogen Adsorption via Spillover in Pt Nanoparticle-Decorated UiO-66 Nanoparticles: Implications for Hydrogen Storage

Abstract: In order to improve room-temperature hydrogen storage, platinum (Pt) nanoparticles (NPs) are doped onto the Zrterephthalate metal−organic framework (MOF) UiO-66 and its derivatives for H 2 adsorption via spillover effect under a highpressure environment. Different MOF synthetic modulators are applied for MOF nanoparticle size manipulation, and surface functionality is designed to improve Pt dispersion. Powder X-ray diffraction shows retained MOF integrity after Pt decoration, and the broad Pt peak indicates we… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
12
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 34 publications
(12 citation statements)
references
References 66 publications
0
12
0
Order By: Relevance
“…This result is in line with the theoretical values and meets our expectations. 43 After incorporating the MOFs into the perovskite, the BET specific surface areas of the UiO-66/perovskite and UiO-66-NH 2 /perovskite composites are significantly reduced, lower than 15 m 2 g −1 , which approaches that of the perovskite. This implies that the perovskite is confined in the MOFs' micropores or that the MOF concentration is low, thus reducing the SSA.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…This result is in line with the theoretical values and meets our expectations. 43 After incorporating the MOFs into the perovskite, the BET specific surface areas of the UiO-66/perovskite and UiO-66-NH 2 /perovskite composites are significantly reduced, lower than 15 m 2 g −1 , which approaches that of the perovskite. This implies that the perovskite is confined in the MOFs' micropores or that the MOF concentration is low, thus reducing the SSA.…”
Section: Resultsmentioning
confidence: 99%
“…UiO-66 was synthesized by a solvothermal process modified from our report. 43 Briefly, zirconium tetrachloride (0.240 g) and terephthalic acid (0.171 g) were dissolved in 60 mL N , N -dimethylformamide (DMF) at room temperature. MOF precipitation can be seen after being heated at 120 °C for 24 hours.…”
Section: Methodsmentioning
confidence: 99%
“…10c). 81 After Pt doping, the H 2 uptake capacity was increased from 0.08 to 0.71 wt%, which XPS studies revealed is due to H 2 spillover in which spiltover H 2 radicals hydrogenate carboxylates in MOF supports. Besides, it was found that the MOF and Pt nanoparticle size have a significant effect on the H 2 adsorbed in the pore.…”
Section: Guest Chemistrymentioning
confidence: 96%
“…Understanding the behaviors of hydrogen adsorption is important for improving hydrogen storage capacity. Moreover, the sorption density on the physisorption of carbonaceous materials is extremely low and has a low hydrogen capacity [141][142][143][144]. Therefore, a progressive strategy is required to create stronger attraction between hydrogen and adsorbents.…”
Section: The Adsorption Models For Hydrogen Storagementioning
confidence: 99%